2012
DOI: 10.1080/03235408.2012.694251
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and infection rate ofMaize streak virusdisease byCicadulina triangularon maize plants and its distribution from the lowest diseased leaf under tropical conditions

Abstract: Several programmes have been initiated for the development of maize varieties with resistance traits of Maize streak virus (MSV) by International Institute of Tropical Agriculture (IITA), Ibadan, and have been released to farmers and research scientists. Therefore, a survey was conducted in five states in the south west of Nigeria (Oyo, Ogun, Ondo, Ekiti and Osun) during the raining planting season to determine the incidence of MSV disease by visual examination and serodiagnostic screening of symptomatic plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The ranges of the titres presented here further indicated that there is variability for resistance to the double viruses in the maize population. ELISA technique has been widely used to detect the presence of viruses in maize with or without disease symptoms (Kumar et al, 2004;Fajinmi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The ranges of the titres presented here further indicated that there is variability for resistance to the double viruses in the maize population. ELISA technique has been widely used to detect the presence of viruses in maize with or without disease symptoms (Kumar et al, 2004;Fajinmi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Incidence was determined using the following equation [23]: Severity was assessed, and the disease index was calculated using the equation proposed by [24,25]:…”
Section: Evaluation Of Agronomic Variablesmentioning
confidence: 99%
“…Disease presence and spread is directly or indirectly affected by various factors (environment and weather condition, insect infestation, and other mechanical factors). Also, Fajinmi et al (2012) reported that the incidence of viral diseases causes great yield loss in crop production in Nigeria.…”
Section: Introductionmentioning
confidence: 99%